6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase Suppresses Neuronal Apoptosis by Increasing Glycolysis and "cyclin-dependent kinase 1-Mediated Phosphorylation of p27 After Traumatic Spinal Cord Injury in Rats. (24th August 2020) - Gao, Liansheng; Wang, Chun; Qin, Bing; Li, Tao; Xu, Weilin; Lenahan, Cameron; Ying, Guangyu; Li, Jianru; Zhao, Tengfei; Zhu, Yongjian; Chen, Gao
Apoptosis is a vital pathological factor that accounts for the poor prognosis of traumatic spinal cord injury (t-SCI). The 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase (PFKFB3) is a critical regulator for energy metabolism and proven to have antiapoptotic effects. This study aimed to investigate the neuroprotective role of PFKFB3 in t-SCI. A compressive clip was introduced to establish the t-SCI model. Herein, we identified that PFKFB3 was extensively distributed in neurons, and PFKFB3 levels significantly increased and peaked 24 h after t-SCI. Additionally, knockdown of PFKFB3 inhibited glycolysis, accompanied by aggravated neuronal apoptosis and white matter injury, while pharmacological activation of PFKFB3 with meclizine significantly enhanced glycolysis, attenuated t-SCI-induced spinal cord injury, and alleviated neurological impairment. The PFKFB3 agonist, meclizine, activated cyclin-dependent kinase 1 (CDK1) and promoted the phosphorylation of p27, ultimately suppressing neuronal apoptosis. However, the neuroprotective effects of meclizine against t-SCI were abolished by the CDK1 antagonist, RO3306. In summary, our data demonstrated that PFKFB3 contributes robust neuroprotection against t-SCI by enhancing glycolysis and modulating CDK1-related antiapoptotic signals. Moreover, targeting PFKFB3 may be a novel and promising therapeutic strategy for t-SCI.